Miss Moriarty, I presume? - Thomas, Sherry (Sherry M.) (Thomas, Sherry (Sherry M.). Lady Sherlock series., 2021)
"Charlotte Holmes comes face-to-face with her enemy when Moriarty turns to her in his hour of need in the USA Today bestselling series set in Victorian England. A most unexpected client shows up at Charlotte Holmes's doorstep: Moriarty himself. Moriarty fears that tragedy has befallen his daughter and wants Charlotte to find out the truth. Charlotte and Mrs. Watson travel to a remote community of occult practitioners where Moriarty's daughter was last seen, a place full of lies and liars. Meanwhile, Charlotte's sister Livia tries to make sense of a mysterious message from her beau, Mr. Marbleton. And Charlotte's longtime friend and ally Lord Ingram at last turns his seductive prowess on Charlotte-or is it the other way around? But the more secrets Charlotte unravels about Miss Moriarty's disappearance, the more she wonders why Moriarty has entrusted this delicate matter to her of all people. Is it merely to test Charlotte's skills as an investigator, or has the man of shadows trapped her in a nest of vipers?"--